
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.



a)\(x+12=-23+5\)
\(< =>x+12+23-5=0\)
\(< =>x+30=0\)
\(< =>x=-30\)

a. 52 + (x+3) = 52
=> x + 3 = 52 - 52
=> x + 3 = 0
=> x = -3
b. 23 + (x-32) = 53 - 43
=> 8 + (x-9) = 125 - 64
=> x - 9 = 125 - 64 - 8
=> x - 9 = 53
=> x = 53 + 9
=> x = 62

n.(2x-5)2=9
(2x-5)2=32
* 2x-5=3 * 2x-5=-3
2x=3+5 2x=-3+5
2x=8 2x=2
x=8:2 x=2:2
x=4 x=1
vậy x=4 hoặc x=1
o.(1-3x )3=-8
(1-3x)3=(-2)3
1-3x=-2
3x=1-(-2)
3x=3
x=3:3
x=1
vậy x=1
a)\(50-3\left(x+4\right)=14\)
\(3\left(x+4\right)=50-14=36\)
\(\left(x+4\right)=36:3=12\)
\(x\) \(=12-4=8\)
b)\(2^{8-x}+75=107\)
\(2^{8-x}\) \(=107-75=32=\pm\left(2\right)^5\)
Vậy\(8-x=5\)hoặc\(8-x=-5\)
\(x=8-5\) \(x=8-\left(-5\right)\)
\(x=3\) \(x=8+5\)
\(x=13\)
Hok tốt!
@Kaito Kid